Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2168.1998.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal dysmotility is not associated with poor outcome after laparoscopic Nissen fundoplication

Abstract: Preoperative manometric assessment of oesophageal motility does not correlate with postoperative outcome, and oesophageal dysmotility should not be regarded as a contraindication to laparoscopic Nissen fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 26 publications
5
43
1
4
Order By: Relevance
“…It has been suggested that manometry could subgroup gastroesophageal reflux disease patients into those requiring partial or total fundoplication treatment [29][30][31] . However, studies have not been able to prove that preoperative manometry could predict postoperative outcome in terms of dysphagia [32][33][34] . Measurement of axial force is more likely to identify patients who would develop postoperative dysphagia, although proof awaits clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that manometry could subgroup gastroesophageal reflux disease patients into those requiring partial or total fundoplication treatment [29][30][31] . However, studies have not been able to prove that preoperative manometry could predict postoperative outcome in terms of dysphagia [32][33][34] . Measurement of axial force is more likely to identify patients who would develop postoperative dysphagia, although proof awaits clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Jobe [40] , in a ten years follow-up, noted a recurrence rate for reflux until 51% in patients treated with partial fundoplication (Toupet and Dor). Moreover, total fundoplication seems not to determinate a higher incidence of postoperative dysphagia compared with the partial wraps, even in patients with impaired peristalsis [41,42] . Patti [43] analysed the long-term results of patients treated with partial versus total antireflux procedures: efficacy was higher for total fundoplication (recurrence of reflux in 4% of patients with total fundoplication versus 19% in patients with partial fundoplication), while the incidence of postoperative dysphagia was similar in both groups, even in patients with impaired esophageal peristalsis (8% Toupet versus 9% Nissen).…”
Section: Discussionmentioning
confidence: 99%
“…Однако, по мнению некоторых авторов, данные манометрии слабо коррелируют с симптомами до антирефлюксной операции и послеоперационными результатами [8,9].…”
Section: © коллектив авторов 2015unclassified